Non-Muslim Divorce Practices in Indonesia: An Examination of Court Procedures and Religious Norms in the Light of Islamic Law - Abdoeh, Nor Mohammad; Riyanta, Riyanta; Wahyuni, Sri (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2025)
In countries with a Muslim-majority population, legal systems often distinguish between Muslims and non-Muslims, particularly in matters of marriage and divorce. This differentiation creates a structural gap for non-Muslims seeking justice in divorce proceedings, as their rights are frequently not accommodated on an equal basis. The primary objective of this article is to examine the application of Haqq al-Insani al-Asasi within non-Muslim divorce cases in Indonesia, focusing on the implementation of the core Islamic values of justice (al-'adl), equality (al-musawah), and human dignity (karamah insaniyyah). This research employs a qualitative prescriptive design with a normative-juridical approach, drawing upon both literature review and judicial decisions as primary data sources. The study analyses 18 District Court rulings from various regions, including Semarang, Salatiga, Cirebon, Kediri, Magelang, Singkawang, Bekasi, and Manado, to assess how Indonesia’s pluralistic legal system accommodates minority rights within its judicial structure. The framework of Islamic Legal Thought concerning justice, equality, and human dignity serves as the methodological tool for analysing the findings, with data primarily derived from official court documents. The results reveal that the application of Haqq al-Insani al-Asasi in non-Muslim divorce cases remains procedural and formalistic, falling short of achieving substantive justice. Court decisions tend to emphasise factual and administrative aspects while neglecting the moral and theological dimensions inherent in the institution of marriage. This leads to a moral legal dissonance, whereby non-Muslim litigants obtain legal certainty but remain spiritually bound according to their faith traditions. The study identifies three primary challenges: the gap between positive law and religious morality, the structural inequality of Indonesia’s dual-court system, and the limited ethical and spiritual sensitivity in judicial reasoning. These findings underscore the need for a more inclusive, human-centred, and substantively just legal reform that bridges state law and moral theology within Indonesia’s pluralistic judicial context.